Corrosion protection of carbon steel using polyaniline composite with inorganic pigments - Ahmed A. Al-Dulaimi,; Shahrir Hashim,; Khan .M.I, (Universiti Kebangsaan Malaysia, 2011)
Two inorganic pigments (TiO2 and SiO2) were used to prepare composites with polyaniline (PANI) by situ polymerization method. PANI and PANI composites with SiO2 and TiO2 were characterized using Fourier transform infrared spectroscopy and X-ray diffraction. The morphology of the synthesized pigments (PANI , PANI-SiO2 and PANI-TiO2) was examined using scanning electron microscopy. Samples were then used as pigments through blending them with acrylic paint and applied on the surface of carbon steel panels. Corrosion was evaluated for coating of carbon steel panels through full immersion test up to standard ASTMG 31. Mass loss was calculated after they have been exposed in acidic media. A digital camera was also used for monitoring corrosion visually on the surface of carbon steel specimens. The results revealed that acrylic paint pigmented by PANI-SiO2 composite was more efficient in corrosion protection for carbon steel compared with the other synthesized pigments